Implementation of the Use of Video Media on the Waist Throw Ability of FIKK UNM Students - Andi Sahrul Jahrir; Muhammad Ivan Miftahul Aziz (Journal Physical Health Recreation (JPHR), 2025)
This study aims to determine the effect of using video tutorial media on improving the ability of waist throw techniques and cognitive learning outcomes of students in wrestling courses. The method used is a quasi-experiment with a pretest–posttest control group design. The research sample consisted of 20 students who were selected purposively, consisting of two groups: the experimental group that was given learning treatment using video tutorials, and the control group that was given conventional learning. The research instruments were in the form of observation sheets for throwing skills and cognitive tests. Data analysis used normality, homogeneity, and t-tests. The results showed that there was a significant increase in the ability of waist throw techniques in the experimental group (an average increase of 25.1 points) compared to the control group (9.2 points). Likewise, cognitive learning outcomes also increased significantly in the experimental group (25.3 points) compared to the control group (12.1 points). The t-test showed a significance value of <0.05 for both variables. It can be concluded that learning using video tutorial media is effective in improving the skills of waist throw techniques and cognitive learning outcomes of students. This media can be an alternative in teaching sports techniques that require visualization and repetition of movements.